Dualisme Standar Halal Dalam Perdagangan Global: Analisis Normatif-Yuridis Fatwa Internasional, Nasional, Dan Implementasi Regional Di Indonesia - Atania Sa’ida El Rosyidah; Hakimuddin Salim (CV. Multi Kreasi Media, 2026)
The global halal industry has experienced rapid growth, creating an increasing need for the harmonization of halal standards across jurisdictions to facilitate international trade. However, differences in fiqh approaches, institutional authority, and legal systems have given rise to the dualism of halal standards. This normative juridical legal research aims to comprehensively analyze the normative framework of halal fatwas at the international level (Islamic International Fiqh Academy/IIFA and Standards and Metrology Institute for Islamic Countries/SMIIC), the national level in Indonesia (Indonesian Council of Ulama/MUI Fatwas and Law No. 33 of 2014 on Halal Product Assurance), and their implementation patterns at the regional level (the Provinces of West Nusa Tenggara and Bali). The findings indicate that there is no substantive theological contradiction between international and national halal fatwas, particularly concerning the use of modern technologies such as stunning in the slaughtering process. The observed dualism is primarily an institutional-juridical phenomenon arising from differences in legal binding force, namely between soft law and harmonization guidelines at the international level, a government-enforced public law system at the national level, and an expressive-devolutive implementation model at the regional level based on regional autonomy.